Potential Cross-Links of Inflammation With Schizophreniform and Affective Symptoms: A Review and Outlook on Autoimmune Encephalitis and COVID-19 - Vasilevska, Veronika; Guest, Paul C.; Schlaaff, Konstantin; Incesoy, Enise I.; Prüss, Harald; Steiner, Johann (Frontiers in Psychiatry, 2021)
Based on current implications of the SARS-CoV-2 pandemic with regards to mental health, we show that biological links exist between inflammation and mental illness in addition to psychoreactive effects. We describe key principles of the biological interaction of the immune system and the mind, as well as the possible routes of viral entry into the brain. In addition, we provide a stepwise scheme for the diagnosis and therapy of autoimmune-encephalitis with schizophrenia-like symptomatology as a general guide for clinical practice and in the specialized scenario of infections, such as those caused by the SARS-CoV-2 virus.